Using small RNA-seq data to detect siRNA duplexes induced by plant viruses - Niu, X.; Sun, Y.; Chen, Z.; Li, R.; Padmanabhan, C.; Ruan, J.; Kreuze, Jan F.; Ling, K.S.; Fei, Z.J.; Gao, S. (MDPI, 2017)
Small interfering RNA (siRNA) duplexes are short (usually 21 to 24 bp) double-stranded RNAs (dsRNAs) with several overhanging nucleotides at both 5'- and 3'-ends. It has been found that siRNA duplexes bind the RNA-induced silencing complex (RISC) and cleave the sense strands with endonucleases. In this study, for the first time, we detected siRNA duplexes induced by plant viruses on a large scale using next-generation sequencing (NGS) data. In addition, we used the detected 21 nucleotide (nt) siRNA duplexes with 2 nt overhangs to construct a dataset for future data mining. The analytical results of the features in the detected siRNA duplexes were consistent with those from previous studies. The investigation of siRNA duplexes is useful for a better understanding of the RNA interference (RNAi) mechanism. It can also help to improve the virus detection based on the small RNA sequencing (sRNA-seq) technologies and to rationally design siRNAs for RNAi experiments.